NLRP3 inflammasome, oxidative stress, and apoptosis induced in the intestine and liver of rats treated with titanium dioxide nanoparticles: in vivo and in vitro study - Abbasi-Oshaghi E (Dove Medical Press, 2019)
Ebrahim Abbasi-Oshaghi,1,2,* Fatemeh Mirzaei,2,* Mona Pourjafar3 1Research Center for Molecular Medicine, Hamadan University of Medical Sciences, Hamadan, Iran; 2Neurophysiology Research Center, Hamadan University of Medical Sciences, Hamadan, Iran; 3Student Research Committee, Hamadan University of Medical Sciences, Hamadan, Iran *These authors contributed equally to this work Purpose: This study evaluated the effects of titanium dioxide nanoparticles (TiO2 NPs) on liver and intestine of normal rats. Methods: Male rats were divided into four groups as follows: 1) control rats, 2) control rats that orally received 10 mg/kg TiO2 NPs, 3) control rats that orally received 50 mg/kg TiO2 NPs, and 4) control rats that orally received 100 mg/kg TiO2 NPs. After 30 days, the NLRP3 inflammasome pathway (NLRP3, caspase-1, and IL-1β), antioxidant pathway (superoxide dismutase [SOD], glutathione peroxidase [GPx], and catalase [CAT]), inflammatory pathway (inducible nitric oxide synthase [iNOS] and tumor necrosis factor-α [TNF-α]), and the apoptosis pathway (p53, Bax, Bcl-2, and caspase-3) were determined in the intestine and liver of the rats. H&E and Masson’s trichrome (MT) staining as well as TUNEL assay were used to examine the liver and the intestine. Biochemical factors, cytotoxicity, ROS generation, and apoptosis rate were also determined in HepG2 and Caco-2 cells.Results: TiO2 NPs in a dose-dependent manner increased cytotoxicity, oxidative stress, and apoptosis rate in Caco-2 and HepG2 cells. The administration of TiO2 NPs significantly reduced antioxidant enzyme activity and gene expressions (SOD, CAT, and GPx) as well as glutathione (GSH) levels and total antioxidant capacity (TAC) in a dose-dependent manner. TiO2 NPs also induced the apoptosis pathway and inflammatory pathway gene expressions and caspase-3 activity in the intestine and liver. TUNEL assay was in agreement with gene expressions. TiO2 NPs also led to morphological changes in the liver and intestine.Conclusion: TiO2 NPs could have cytotoxic effects on the intestine and liver structure and function by inducing oxidative stress, inflammation, and apoptosis. Keywords: caco-2 cells, hepg2 cells, gene expression, rat